Developing science teachers’ enacted pedagogical content knowledge through integration of student feedback into the Refined Consensus Model of pedagogical content knowledge - Daniel Hartmuth; Rifat Mehreen Amin; Daniel Schlichting; Svenja Schött; Jonathan Haudenschild; Helmut Küchenhoff; Birgit J. Neuhaus (Cogent Education)
Developing Pedagogical Content Knowledge (PCK) is a facet of teachers′ professional competence. The Refined Consensus Model of PCK (RCM) emphasises a cyclical process structure to develop an individual’s enacted PCK (ePCK) and the plan-teach-reflect cycle must be systematically adjusted by means of feedback loops. Simple graphic visualisation of student feedback over time provide the information for teachers to improve ePCK. The research gap lies in providing teachers with an actionable cyclic feedback process and evaluating its effectiveness. In an intervention study with 28 in-service science teachers and 137 lessons at secondary schools in Bavaria, Germany, we analysed the effect of student feedback for developing ePCK. We compared two types of visual feedback for how they influenced the teacher’s ability in the classroom, indirectly measured as a change in the students’ assessment of lesson quality. Lesson ratings improved slightly but not significantly when teachers used the feedback tool. The high intra-class correlation of consecutive lesson assessments supported the use of rolling average curves in the graphics. We conclude that science teachers can foster ePCK with the help of student feedback, which empowers teachers in practice and serves as a valuable tool in research to investigate the development of ePCK in greater detail.